The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s13227-020-00157-8
|View full text |Cite
|
Sign up to set email alerts
|

Can the anatomy of abnormal flowers elucidate relationships of the androecial members in the ginger (Zingiberaceae)?

Abstract: Background: Interpretation of the floral structure of Zingiberaceae has long concentrated on the relationships of the androecial members. It suggested that labellum is composed of two structures rather than three or five, and glands are interpreted either as gynoecial part or as androecial members. Methods: Serial sections were used to observe the vasculature of normal and two-staminate flowers in Alpinia intermedia 'shengzhen'. Floral diagrams were drawn to interpret the morphological category of the floral o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…In Zingiberales, abnormal flowers provide material evidence to study the homeosis through comparative anatomical analyses. Compared with organs in other whorls, androecial members show a much wider variation in abnormal flowers, which conforms to the androecial modifications seen in this order (Rao 1963; Maas 1977; Song et al 2003; Li et al 2020). In this research, comparisons between the abnormal flowers and the normal flowers clearly indicated homologies between the androecial members.…”
Section: Discussionsupporting
confidence: 75%
“…In Zingiberales, abnormal flowers provide material evidence to study the homeosis through comparative anatomical analyses. Compared with organs in other whorls, androecial members show a much wider variation in abnormal flowers, which conforms to the androecial modifications seen in this order (Rao 1963; Maas 1977; Song et al 2003; Li et al 2020). In this research, comparisons between the abnormal flowers and the normal flowers clearly indicated homologies between the androecial members.…”
Section: Discussionsupporting
confidence: 75%
“…Song et al [ 41 ] described six types of abnormal flowers in Alpinia ; these abnormalities include flowers with 2 fertile stamens, 1.5 stamens, 1 stamen, single stamen with only one theca (½ stamen), and fertile stamen completely absent as well as the occurrence of twin flowers forming mirror images. Li et al [ 42 ] recently reported two-staminate aberrant flowers in a cultivar A. intermedia ‘shengzhen’. These aberrant flowers share with one another alterations in the form of the androecial members that indicate common deviations from a canalized developmental pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Controlling the flowering time and understanding the physiological mechanism of the induction of flowers are essential to the tourism, research, and flower industries [1]. In recent years, many researchers have studied the flowering process, including flower morphological structure, nutrients, mineral elements, enzymes, and relevant genes in flowers, so as to reveal the biological characteristics and regulate the flowering period of different plants [2][3][4][5]. Based on the study of flower morphology in the genus Capsella, Neuffer and Paetsch [6] specifically disclosed the petal size, pollen number, stigma length, and so on in Capsella grandiflora, C. rubella, and C. bursa-pastoris.…”
Section: Introductionmentioning
confidence: 99%